Seismic Load Tests on Exterior Beam-Column Connections of Existing RC Structures - Cosgun, Turgay; Cosgun, Cumhur; Kanishka, Abdulrauf; Mangir, Atakan; Sayin, Baris; TÜRK, AHMET MURAT (Croatian Association of Civil Engineers, HSGI, 2019)
Recommendations for enhancement of performance of RC beam-column joints under seismic effects are presented in this study. The aim is to evaluate the use of low-strength concrete with plain bars without stirrups in the joints. An additional aim is to study behaviour of joints in the aforementioned conditions under cyclic loading. Five specimens with various reinforcement configurations were produced and tested in the experimental process. Based on results obtained in the study, it is concluded that the stirrup arrangement in the joints, and the use of at least 90-degree hooks in longitudinal reinforcement of beams, are critical parameters for the performance of existing structures.
Keywords: RC Beam-Column Joint